Appreneur Secrets to Success in the App Store - Pierce, Taylor; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
You are interested in making an app. You have read all of the stories of successful developers and appreneurs. You are determined to get a piece of the pie. The world of apps is the fastest growing market in the world today, and it is here to stay. The best part is you can get in on it! Now what if I told you that without the knowledge contained in this book the odds of you making a profit are slim to none? What if I also told you that you probably wouldn$1 (Bt break even? There is more to apps than most people think. The average person assumes that if they make an app, they will instantly become a millionaire. The truth is without the knowledge from years of successes and failures, you just won$1 (Bt know where to begin. Appreneur book contains tips, tricks, secrets, and stories from the top developers, appreneurs, and companies from around the globe. After reading this book, you will have the knowledge to bring your idea to life, market it, promote it, and sell it in a way that would have otherwise been impossible.s
Keywords: Computer science; Computer Science; Computer Science, general